Koperasi Syariah : Solusi Ekonomi Berbasis Syariah untuk Kesejahteraan Umat - Syarifa Khaerunnisa; Amiruddin Amiruddin; Mukhtar Lutfi (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2025)
Sharia cooperatives are Sharia-based economic institutions that play a strategic role in empowering the economy of the Muslim community. By adhering to principles such as the prohibition of riba (usury), gharar (uncertainty), and maysir (gambling), as well as implementing profit-sharing systems (mudharabah or musharakah), Sharia cooperatives provide a fair, transparent, and inclusive alternative to support economic activities in society. These cooperatives aim not only to achieve financial gains but also to fulfill social missions, such as poverty alleviation, equitable welfare distribution, and holistic improvement of the community’s quality of life. Various products and services offered—such as Sharia savings, halal financing, and Sharia-compliant investments—provide financial solutions that align with Islamic values and meet societal needs. Nevertheless, the implementation of Sharia cooperatives faces several challenges, including limited public understanding, competition with conventional financial institutions, and constraints in human resources and capital. Through public education, capacity building for cooperative managers, and comprehensive government policy support, Sharia cooperatives hold great potential to become a key instrument in fostering a more just, equitable, and sustainable economy. This study emphasizes the importance of integrating Sharia values into cooperative management to ensure its contribution to the sustained welfare of the community.